Role of Carbamazepine in the Symptomatic Treatment of Subacute Sclerosing Panencephalitis: A Case Report and Review of the Literature - Sandhya Ravikumar; John Ross Crawford (Case Reports in Neurological Medicine)
We describe the clinical presentation and clinical course of subacute sclerosing panencephalitis in a 13-year-old previously healthy boy who recently immigrated to the United States from Iraq. He presented with macular retinopathy, followed by progressive myoclonus and encephalopathy. After extensive workup, a diagnosis of subacute sclerosing panencephalitis was suspected by the presence of period epileptiform discharges on electroencephalogram and confirmed by elevated measles titers in the cerebrospinal fluid. Combination immunomodulatory therapy with isoprinosine, ribavirin, and intra-Ommaya interferon alpha did not result in clinical improvement. Within days following the administration of carbamazepine, there was remarkable improvement in the myoclonus and he was able to ambulate independently for a period of 4 months at which time he unfortunately progressed to a vegetative state. This case highlights the importance of carbamazepine as a potential first line symptomatic treatment of subacute sclerosing panencephalitis and provides a review of the literature on the subject.